LES ÉCOFÉMINISMES COMME OUTILS D'ÉMANCIPATION ? - Socios Engagé·e·s (2022)
Et s'il y avait plusieurs écoféminismes ? Mouvement en vogue, porté notamment par des figures politiques et médiatiques, "l'écoféminisme" suscite curiosités et interrogations, tant ses représentations peuvent prendre des formes diverses, incarnées par des idéologies différentes. C'est le constat de Myriam Bahaffou, écoféministe, chercheuse en philosophie féministe et autrice de l'essai "des paillettes sur le compost, écoféminismes au quotidien", invitée par Le Média. Son livre aborde une écologie et un féminisme aux intersections du véganisme, des luttes décoloniales, queer et anti-validistes, mais aussi loin des jeux de pouvoir institutionnels. 🔴 Le Média TV est LE média des luttes et des combats. Pour fonctionner, il ne peut compter que sur ses abonné.e.s et ses donateurs. Faites un don ou abonnez-vous à partir de 5€/mois ➡️ https://lemediatv.fr/soutien
Keywords: approches et analyses; cours; discipline; environnement; militance; philosophie; pol5480; premier cycle; sciences humaines; thématiques; écoféminisme

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

La nature a-t-elle un genre ? Variétés d’écoféminisme - Larrère, Catherine (Cahiers du Genre, 2015)
L’écoféminisme est un mouvement qui s’est développé surtout dans les pays anglophones et qui, en montrant la liaison entre l’oppression des femmes et la domination de la nature, cherche à les combattre ensemble. Cependant, le féminisme s’est largement construit contre la naturalité du sexe, puis du genre. Écologiser le féminisme, n’est-ce pas l’ouvrir à la naturalisation ? En examinant l’écoféminisme culturel (principalement américain), puis social (plus présent dans le Sud, et liant la domination des femmes et de la nature au colonialisme et à l’impérialisme), nous montrerons comment la réflexion féministe sur la nature tend à mettre en question l’évidence de celle-ci, sans en abandonner la référence.
Keywords: approches et analyses; discipline; environnement; nature; philosophie; projet charge mentale; ressource en ligne; santé; sciences humaines; thématiques; écoféminisme

Feminist epistemology after postmodernism: Critiquing science, technology and globalisation - Braidotti, Rosi (Interdisciplinary Science Reviews, 2007)
This article provides a reasoned overview of contemporary developments within feminist theories of the subject after the decline of postmodernist thought. It stresses the foundational importance of feminist situated epistemology, and hence of a brand of materialism that stresses embodiment and embedded perspectives. The article explores neo-materialist feminist theories in a number of areas, with special emphasis on science and technology studies and critiques of globalisation. It argues that the neo-materialist trend results in a new call for an ethics attuned to the complexity of our era.
Keywords: approches et analyses; bio-technologie; discipline; environnement; féminisme matérialiste; philosophie; postmodernisme; projet charge mentale; ressource en ligne; sciences humaines; thématiques; épistémologie

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme

Feminism and ecological communities: an ethic of flourishing - Cuomo, Chris J. (Routledge, 1998)
Feminism and Ecological Communities presents a bold and passionate rethinking of the ecofeminist movement. It is one of the first books to acknowledge the importance of postmodern feminist arguments against ecofeminism whilst persuasively preseenting a strong new case for econolocal feminism. Chris J.Cuomo first traces the emergence of ecofeminism from the ecological and feminist movements before clearly discussing the weaknesses of some ecofeminist positions. Exploring the dualisms of nature/culture and masculing/feminine that are the bulwark of many contemporary ecofeminist positions and questioning traditional traditional feminist analyses of gender and caring, Feminism and Ecological Communities asks whether women are essentially closer to nature than men and how we ought to link the oppression of women, people of colour, and other subjugated groups to the degradation of nature. Chris J.Cuomo addresses these key issues by drawing on recent work in feminist ethics as well as teh work of diverse figures such as Aristotle, John Dewey, Donna Haraway adn Maria Lugones. A fascinating feature of the book is the use of the metaphor of the cyborg to highlight the fluidity of the nature/culture distinction and how this can enrich econfeminist ethics and politics. An outstanding new argument for an ecological feminism that links both theory and practice, Feminism and Ecological Communities bravely redraws the ecofeminist map. It will be essential reading for all those interested in gender studies, environmental studies and philosophy.
Keywords: approches et analyses; com5170; cours; discipline; environnement; philosophie; postmodernisme; premier cycle; sciences humaines; thématiques; écoféminisme

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme